Strategi Pengembangan Wisata Kuliner di Pasar Bambu Desa Wisata Bonjeruk sebagai Upaya Meningkatkan Jumlah Kunjungan Wisatawan - Lale Aulia Soleha; Alip Suroto; I Gusti Ayu Agung (Jurnal Perhotelan dan Pariwisata, 2026)
Culinary tourism is an essential attraction in the development of sustainable tourism villages. Pasar Bambu in Bonjeruk Village, Central Lombok, offers traditional culinary experiences and a strong cultural atmosphere that can enhance tourist visits, yet its management still faces several challenges. This study aims to analyze culinary tourism development strategies at Pasar Bambu and examine efforts to manage facilities and infrastructure in order to increase visitor numbers. The research employed a descriptive qualitative method, utilizing observation, in-depth interviews, documentation, and literature review, with market staff and tourists as informants. The findings indicate that development strategies include improving physical facilities, organizing cultural events, promoting through digital media, providing community training and empowerment, and collaborating with external partners. Data revealed a significant 58% increase in tourist visits in 2024 compared to the previous year. However, challenges remain, including limited funding, low community participation in facility maintenance, and minimal external support. The study concludes that integrated management strategies combined with effective digital promotion and community involvement are crucial to strengthening Pasar Bambu’s position as a sustainable culinary tourism destination.